Faktor–Faktor Yang Berhubungan Dengan Tingkat Kecemasan Pasien Kanker di Poli Bedah Onkologi Rumah Sakit Hasan Sadikin Bandung - Sri Ramdaniati; Caturwati Nugraheni (Jurnal Medika Cendikia, 2014)
Cancer is an abnormal growth of tissue that extends beyond the normal tissue that failed to meet the normal function of cells in the tissue. Patients usually come to the doctor in an advanced stage that the disease refractory, requires prolonged treatment and high cost. This happens because the patient and family do not understand and misconceptions about cancer. Conditions so that trigger cancer patients have psychological disorders such as anxiety. This study aimed to determine the relationship between the factors of gender, age, level of education, level of income / socio-economic and level of knowledge with the level of anxiety in cancer patients. The study was conducted by using the correlation method with cross sectional design performed on 55 patients with cancer in the surgical oncology polyclinic Hasan Sadikin Hospital. The results showed that of the five variables studied, there are four that have a significant relationship with the level of anxiety that age, level of education, level of income / social economy and the level of knowledge (p <0.05). While the gender factor is not associated statistically (p> 0.05). Based on these studies, it is recommended for nurses to provide health education by taking into account factors that affect the level of anxiety.